Penilaian Mahasiswa Keperawatan Tentang Standardized Patient Dalam Ujian OSCA Di Universitas Muhammadiyah Surakarta - Nugraha, Ega, Enita Dewi S.Kep.,Ns.,MN (2017)
Background: Objective structured clinikal assessment (OSCA) is an attempt to evaluate the learning outcomes based curriculum aimed at assessing the competence of student competencies and clinical skills of students in an objective and structured. The use of standardized patients in the process of OSCA done so that students are accustomed to face with the patient in the clinic without compromising patient safety. This study aims to describe nursing students on standardized assessment test OSCA patient. Methods: This study was a descriptive study using cross sectional approach. The study population was a student nursing S1 one semester in the Faculty of Health Sciences University of Muhammadiyah Surakarta totaling 129 students. Research sample were 60 students who obtained by simple random sampling technique. Collecting data using questionnaires, while data analysis using quantitative descriptive test Result: Results from this study is assessment of nursing students on standardized patient in OSCA on physical details SP is positive (96.7%), the SP is a positive psychological details (100%), the social detail SP is positive (80%). Conclusion: Conclusion of the study is to provide an assessment of students more good than bad judgment. However, the role of Standardized patient in FIK UMS according to students has been good. Standardized patient bias acting optimally and master a given scenario. Required training or training sufficient for standardized patient really appreciate the role and control of the scenario that reasonably assist students in exploring the history of the disease and make a difference in diagnosis.